1976
DOI: 10.1136/bmj.1.6009.550
|View full text |Cite
|
Sign up to set email alerts
|

Streptokinase in central retinal vein occlusion: a controlled clinical trial.

Abstract: 550BRITISH MEDICAL JOURNAL 6 MARCH 1976 waiting time for transplantation-now averaging two years'-are self evident. This series shows the value of HLA matching of donor and recipient for two, three, or four antigens, which was particularly important for the long-term survival of the transplants. As 77°o f transplant failures after 12 months were due to rejection it appears that close HLA matching of donor and recipient confers considerable benefit in decreasing kidney loss due to late rejection. The import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 7 publications
1
44
0
2
Order By: Relevance
“…Our findings parallel those reported by other investigators who found a beneficial effect of thrombolysis in retinal vein occlusion. Kohner et al [23]investigated the efficacy of streptokinase in CRVO in a controlled clinical trial. The visual outcome in their treatment group was significantly better than in controls; however, the use of streptokinase resulted in vitreous hemorrhage with permanent loss of vision in 3 of 20 patients [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings parallel those reported by other investigators who found a beneficial effect of thrombolysis in retinal vein occlusion. Kohner et al [23]investigated the efficacy of streptokinase in CRVO in a controlled clinical trial. The visual outcome in their treatment group was significantly better than in controls; however, the use of streptokinase resulted in vitreous hemorrhage with permanent loss of vision in 3 of 20 patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Kohner et al [23]investigated the efficacy of streptokinase in CRVO in a controlled clinical trial. The visual outcome in their treatment group was significantly better than in controls; however, the use of streptokinase resulted in vitreous hemorrhage with permanent loss of vision in 3 of 20 patients [23]. In another study, a more favorable outcome after treatment of CRVO and branch retinal vein occlusion with streptokinase in comparison to anticoagulant therapy with heparin was observed [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrinolytic treatment of RVO based on the thrombotic pathogenesis of the disease and administration of fibrinolytic agent may the recanalize the obstructed vein by lysing the thrombus [12] . Some studies showed that despite systemic thrombolitic agents have beneficial effects on the blood flow of the obsructed retinal vein and improvement in visual acuity, these systemic agents associated with some side effects as massive subretinal haemorrhage, vitreous haemorrhage, gastrointestinal haemorrhage, serebral haemorrhage even death [9,[13][14][15] . Because of the serious side effects, systemic fibrinolytic agents are not prefered for RVO anymore.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Because of systemic risks, this approach has not been widely adopted or definitively studied. To limit the systemic side effects, investigators have used other approaches to deliver the thrombolytic agent locally, such as intravitreal injection and intravenous retinal cannulization.…”
Section: Introductionmentioning
confidence: 99%